Room-Temperature Mg-Ion Conduction Through Molecular Crystal MgN(SO2CF3)22(CH3OC5H9)2 - Ota, Takaaki; Uchiyama, Shota; Tsukada, Keiichi; Moriya, Makoto (Frontiers in Energy Research, 2021)
Molecular crystals have attracted increasing attention as a candidate for innovative solid electrolytes with solid-state Mg-ion conductivity. In this work, we synthesized a novel Mg-ion-conducting molecular crystal, MgN(SO2CF3)22(CH3OC5H9)2 (Mg(TFSA)2(CPME)2), composed of Mg bis(trifluoromethanesulfonyl)amide (Mg(TFSA)2) and cyclopentyl methyl ether (CPME) and elucidated its crystal structure. We found that the obtained Mg(TFSA)2(CPME)2 exhibits solid-sate ionic conductivity at room temperature and a high Mg-ion transference number of 0.74. Contrastingly, most Mg-conductive inorganic solid electrolytes require heating above 150–300 °C to exhibit ionic conductivity. These results further prove the suitability of molecular crystals as candidates for Mg-ion-conducting solid electrolytes.